Quality Characteristics and Antioxidant Activities of Six Types of Korean White Wine - Sae-Byuk Lee (Foods, 2023)
The cultivation of European grape cultivars suitable for winemaking in Korea presents challenges due to factors such as climate, soil conditions, precipitation, and sunlight. Consequently, Korea has traditionally resorted to adding sugar to its wine production to counteract the low sugar content in Korean grapes, yielding lower-quality wines. However, recent success in the cultivation of five European grape cultivars and the development of the domestic grape cultivar Cheongsoo have increased the possibility of achieving high-quality Korean wines. This study aimed to explore the potential of European grape cultivars and Cheongsoo as wine grapes in Korea. This study also conducted sensory evaluation and analyzed the physicochemical properties of the grapes and wines, including antioxidant capacity and color. Despite originating from the same vineyard, the composition of grapes and wines, including volatile aromatic compounds, significantly differed among the grape cultivars. In particular, Vidal wine exhibited superior antioxidant capacity compared with other wines. Moreover, Cheongsoo wine showed higher levels of essential volatile aromatic compounds, such as monoterpenes, than other wines. Sensory evaluation of these two wines also revealed excellent results. In conclusion, these findings hold promise for enhancing the diversity of Korean white wine and fostering growth in the wine industry.